Barriers to entry for firms in the agricultural sector of Sonora - Catalán Dibene, César Gioberti (2021)
This aim of this paper is to analyze if the firms of the agricultural sector located in the Northwest México impose entry barriers (BE) as a strategic behavior (CE). Methodology. A survey to informants of 32 firms of the agricultural sector was applied; the obtained data were used to make a hierarchical grouping and three groups of firms were defined according to BE identified. Results. Three groups of firms and thirteen BE imposed by firms in the agricultural sector were identified. Conclusions.  The use of CE by the incumbent firms is considered BE, mainly those related with absolute cost, land concentration and vertical and horizontal integration. Based on the performed analysis, the land concentration will become in the main BE, due to the intensive use of natural resources